(untitled) (Journal of the College of Basic Education, 2026)
This study aimed to identify the effect of applying educational stations according to the Skills-Based Learning (SBL) model on learning some basic handball skills among students of the College of Physical Education and Sports Sciences. The researcher adopted the experimental method using a design with two groups: an experimental group and a control group. The research sample consisted of (42) students who were randomly assigned to the two groups. The educational program based on educational stations was applied to the experimental group, while the control group was taught using the traditional method. The skills under investigation included dribbling, passing and receiving, and shooting accuracy. The results revealed statistically significant differences in favor of the experimental group in all the studied skills. This improvement is attributed to the effectiveness of educational stations in increasing actual practice time and organizing skill learning. The study concluded that Skills-Based Learning is one of the effective approaches for improving motor performance in handball. Accordingly, the researcher recommended adopting educational stations based on the Skills-Based Learning model in teaching basic handball skills and shifting from traditional methods to modern instructional models based on active learning.